A retrospective study of vertebral fracture and luxation in dogs presented to University Veterinary Hospital, Universiti Putra Malaysia in 2015 to 2017 - Mohd Asri, Murshidah; Lau, Seng Fong; Ikhwan, Saufi Azahari; Shafie, Intan Nur Fatiha (Universiti Putra Malaysia Press, 2021)
To date, there is data paucity on canine vertebral fracture and luxation (VFL) in the local setting. Therefore, it was hypothesized that the geographical location and stray dog population would influence VFL cases in the University Veterinary Hospital, Universiti Putra Malaysia (UVH, UPM). This study aimed to describe the incidence and characteristics of VFL in dogs presented to UVH, UPM. Medical records, including radiographic images of 74 dogs between 2015 to 2017, were reviewed. VFL dominated the spinal cord disease in dogs at 49% (n = 36/74), exceeding intervertebral disc disease (IVDD) and acute noncompressive nucleus pulposus extrusion (ANNPE). Half of VFL cases were contributed by intact male, small breed dogs aged more than one-year-old, with 52% (n = 11/19) of cases caused by vehicular accidents. Almost two-thirds (n = 21/36) of dogs with VFL were outdoor or stray dogs, and the Th3-L3 region was the most susceptible (52%, n = 19/36) for VFL. More than 70% (n = 25/36) of the patients had unstable fractures, highly associated with severity. In conclusion, the occurrence of VFL in UVH, UPM is three times higher than reported in western countries and most likely contributed by a large number of outdoor and stray dogs.